DIGITAL-BASED PRODUCTIVE ZAKAT DISTRIBUTION MODEL IN ENHANCING THE EMPOWERMENT OF MSMEs FROM THE ISLAMIC ECONOMICS PERSPECTIVE - Alfin Maulana (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
Productive zakat has increasingly gained attention as an alternative instrument for sustainable economic empowerment, particularly for micro, small, and medium enterprises (MSMEs). Unlike consumptive zakat, productive zakat emphasizes long-term impacts by strengthening beneficiaries’ productive capacity. This study aims to critically examine recent developments in productive zakat distribution models and analyze their relevance in enhancing MSME empowerment from an Islamic economic perspective. The study employs a qualitative approach through an in-depth literature review and analytical synthesis of empirical studies published between 2021 and 2025. The findings indicate that productive zakat programs that integrate capital assistance, business mentoring, and digital management systems tend to generate more sustainable economic outcomes for beneficiaries. However, the effectiveness of such programs remains uneven due to institutional capacity constraints and limited post-distribution monitoring. This study argues that productive zakat should be positioned not merely as a charitable mechanism, but as a structured Islamic social finance instrument that requires professional governance and measurable performance indicators. The study contributes to the discourse on Islamic economic development by offering a critical reflection on the future direction of productive zakat management